MiR‐29‐mediated elastin down‐regulation contributes to inorganic phosphorus‐induced osteoblastic differentiation in vascular smooth muscle cells. (27th November 2015) - Sudo, Ryo; Sato, Fumiaki; Azechi, Takuya; Wachi, Hiroshi
Abstract : Vascular calcification increases the risk of cardiovascular mortality. We previously reported that expression of elastin decreases with progression of inorganic phosphorus (Pi)‐induced vascular smooth muscle cell (VSMC) calcification. However, the regulatory mechanisms of elastin mRNA expression during vascular calcification remain unclear. MicroRNA‐29 family members (miR‐29a, b and c) are reported to mediate elastin mRNA expression. Therefore, we aimed to determine the effect of miR‐29 on elastin expression and Pi‐induced vascular calcification. Calcification of human VSMCs was induced by Pi and evaluated measuring calcium deposition. Pi stimulation promoted Ca deposition and suppressed elastin expression in VSMCs. Knockdown of elastin expression by shRNA also promoted Pi‐induced VSMC calcification. Elastin pre‐mRNA measurements indicated that Pi stimulation suppressed elastin expression without changing transcriptional activity. Conversely, Pi stimulation increased miR‐29a and miR‐29b expression. Inhibition of miR‐29 recovered elastin expression and suppressed calcification in Pi‐treated VSMCs. Furthermore, over‐expression of miR‐29b promoted Pi‐induced VSMC calcification. RT‐qPCR analysis showed knockdown of elastin expression in VSMCs induced expression of osteoblast‐related genes, similar to Pi stimulation, and recovery of elastin expression by miR‐29 inhibition reduced their expression. Our study shows that miR‐29‐mediated suppression of elastin expression in VSMCs plays a pivotal role in osteoblastic differentiation leading to vascular calcification. Abstract : This basic study investigated the mechanism of elastin down‐regulation in the progression of calcification, focusing on clarifying the effect of microRNA; miR‐29 which is the regulator of elastin expression. We demonstrated that elastin down‐regulation, which are regulated by miR‐29, played a pivotal role in the progression of vascular smooth muscle cells calcification via osteoblastic differentiation.